SOLUTIONS TO THE CHALLENGES IN DESIGNING CONTEMPORARY RESIDENTIAL BUILDINGS - Madumarova Marg‘ubaxon (Bright Mind Publishing, 2025)
This paper addresses the multifaceted challenges encountered in the design of contemporary residential buildings and proposes integrated solutions rooted in sustainability, cultural sensitivity, spatial adaptability, and technological innovation. Through a qualitative, comparative methodology supported by international case studies and expert perspectives, the study identifies key constraints such as limited urban space, environmental imperatives, material costs, socio-cultural incompatibilities, and technological disparities. The results highlight the importance of flexible spatial configurations, vernacular integration, passive and active sustainable strategies, and inclusive digital tools to meet the evolving demands of modern housing. Moreover, the discussion underscores the necessity for participatory design practices and interdisciplinary collaboration to ensure that residential architecture remains responsive to both global design standards and localized human needs. The paper concludes that future-ready housing must go beyond aesthetics and technical performance to embrace a holistic paradigm where culture, climate, technology, and equity intersect—thus promoting not only livable structures but also resilient and meaningful domestic environments.
Keywords: Contemporary residential design; Housing challenges; Sustainable architecture; Cultural adaptation; Space optimization; Smart homes; Vernacular integration; Participatory design; Urban density; Affordable housing.